The Craving and Excitement of Social Networking Sites Addicts: Based on Cue-Reactivity - Leng, Yexi; He, Xi; Zhu, Baijie; Li, Ping; Xiao, Chuan; He, Weiqi (Frontiers in Psychology, 2019)
Everyone benefits from social networking as a daily tool, but there are potential addictions. However, little is known about the craving and excitability of social networking sites addiction, and changing regulars in craving. The study consisted of two experiments that used cue-reactivity paradigm to study the cravings and excitement of social networking sites addiction and the changing regulars in cravings. Sixty subjects were divided into high-score group and low-score group. In Experiment 1, all subjects evaluated word clues. The results showed that the SNS-related clues only induced the craving and excitability of high-score group, but not low-score group, and the craving is fluctuating. Furthermore, in Experiment 2, image clues were used. The results showed the craving induced by image clue is significantly higher than the craving induced by word clue, and there is no difference in excitability. Taken together, our findings suggest the SNS-related stimulation, especially image clues, could significantly induce subjects for the craving and excitability of social networks, and the craving is fluctuating.